Staphylococcus aureus Bacteremia Complicated by Psoas Abscess and Infective Endocarditis in a Patient with Atopic Dermatitis. (10th December 2017) - Tsuboi, Ichiro; Yumoto, Tetsuya; Toyokawa, Tatsuya; Matsueda, Katsunori; Horii, Joichiro; Naito, Hiromichi; Nakao, Atsunori
Abstract : The close relationship between atopic dermatitis (AD) and infective endocarditis (IE) has been implicated. Staphylococcus aureus colonization is frequently seen observed in AD patients' skin lesions. Although a case of IE due to S. aureus bacteremia in an AD patient has been sporadically reported, a case of S. aureus bacteremia complicated by psoas abscess and IE has not been previously reported. A 42-year-old man with a history of AD presented to our hospital complaining of fever, fatigue, chills, lower right back pain, and poor appetite for a week. His blood cultures showed growth of S. aureus . On day 3, the patient presented acute cardiac failure and was diagnosed with IE based on echocardiogram examination. Since the patient's cardiac failure did not respond to medication, an emergency surgery was performed on the fourth day of hospitalization. The patient underwent successful surgical treatment of the heart lesions and subsequent percutaneous drainage of psoas abscess and received intensive antibiotics, which successfully improved his condition. Our report emphasizes awareness of the association between AD and invasive S. aureus infections.